2018
DOI: 10.1155/2018/3025683
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life in Individuals Transferred from a Needle Exchange Program and Starting Opioid Agonist Treatment

Abstract: Background Opioid agonist treatment (OAT), for the treatment of heroin dependence, has been reported to improve overall health and lower mortality. Drug use and retention in treatment have often been used as measures of treatment success. More recently, however, researchers have suggested that measurements of quality of life should be an outcome in substance use treatment evaluations. In a recent randomized controlled trial we demonstrated high rates of successful rapid referral from a needle exchange program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
4
0
2
Order By: Relevance
“…Previous research has revealed that HRQoL improves considerably at OAT treatment initiation and the first few months [44]: however, not much research to date has investigated the long-term effect of OAT on patients' HRQoL [7,22,29]. For instance, one study among patients on methadone maintenance treatment found that QoL increased markedly in the beginning of the observation, but decreased after 6 months [45] while other studies only saw improvements in the beginning of observation [27,46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that HRQoL improves considerably at OAT treatment initiation and the first few months [44]: however, not much research to date has investigated the long-term effect of OAT on patients' HRQoL [7,22,29]. For instance, one study among patients on methadone maintenance treatment found that QoL increased markedly in the beginning of the observation, but decreased after 6 months [45] while other studies only saw improvements in the beginning of observation [27,46].…”
Section: Discussionmentioning
confidence: 99%
“…Non-fatal OD is highly prevalent among people who use drugs; experienced by 17–68% and witnessed by 50–96% [ 1 ]. In Sweden, self-reports show that over 70% of people injecting heroin have survived at least one OD [ 39 , 40 ]. These numbers indicate that there may be many OD cases never noted in the patient register.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the OST patient population in Malmö has a high burden of psychiatric and physical morbidity, comparable to international data. Previous research from Skåne county has shown that 72% of OST patients in Malmö had experienced at least one overdose and 31% had tried to commit suicide [ 46 ].…”
Section: Discussionmentioning
confidence: 99%